2016
DOI: 10.1080/13658816.2016.1191637
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of a high-resolution analysis of transit accessibility

Abstract: Accessibility is an important consideration in sustainable mobility policies, particularly for transit users. Measures suggested in the literature are based on coarse aggregate spatial resolution of traffic analysis zones that is sufficient for managing car travels only. To reflect a human door-to-door travel, transit accessibility demands an explicit view of the location of origin, transit stops and destination, as well as of the temporal fit between transit lines timetable and traveler's needs. We thus estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Other studies have generated combined measures of socio-economic disadvantage at a neighbourhood level to compare with accessibility measures to highlight where gaps in transit accessibility align with social need (Foth et al, 2013;Fransen et al, 2015). Research has also shown that the travel modes available to an individual makes a substantial difference in terms of access to destinations, particularly the disparity between transit riders and those who have regular use of a private vehicle (Benenson et al, 2011;Golub & Martens, 2014;Benenson et al, 2017). There have been a number of academic reviews which have discussed how social equity, and in particular improving people's access to destinations, should be further incorporated into transportation plans and policy to reduce inequalities and foster social and economic inclusion (Wee & Geurs, 2011;Karner & Niemeier, 2013;Manaugh et al, 2015;Pereira et al, 2017).…”
Section: Inequalities In Transport Accessibilitymentioning
confidence: 99%
“…Other studies have generated combined measures of socio-economic disadvantage at a neighbourhood level to compare with accessibility measures to highlight where gaps in transit accessibility align with social need (Foth et al, 2013;Fransen et al, 2015). Research has also shown that the travel modes available to an individual makes a substantial difference in terms of access to destinations, particularly the disparity between transit riders and those who have regular use of a private vehicle (Benenson et al, 2011;Golub & Martens, 2014;Benenson et al, 2017). There have been a number of academic reviews which have discussed how social equity, and in particular improving people's access to destinations, should be further incorporated into transportation plans and policy to reduce inequalities and foster social and economic inclusion (Wee & Geurs, 2011;Karner & Niemeier, 2013;Manaugh et al, 2015;Pereira et al, 2017).…”
Section: Inequalities In Transport Accessibilitymentioning
confidence: 99%
“…As well as this, several options for the method of travel are available. Even though the majority of studies use only the fastest connection from the given departure time (e.g., [25]), this option is not preferred for all people and all purposes. Our model deals with a specified time interval and finds not just the fastest connection within this interval, but also the latest, the earliest, the shortest, a random and a "comfort" option.…”
Section: Discussionmentioning
confidence: 99%
“…Walking to and from stops is included as an obligatory part of each PT trip (similar to [25]). Furthermore, walking directly (hereafter referred to as pedestrian mode) between the origin and the destination is evaluated, which is important for shorter trips.…”
Section: Concept Of Modellingmentioning
confidence: 99%
“…Besides, due to both data availability and computing limitations, most studies have used rather rough estimates of travel time when calculating potential accessibility [16]. The problem with such an approach is that it ignores traffic congestion, transfer time, necessary walking time, etc., which may substantially alter the travel time results [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%